A comparative study of meta-heuristic and conventional optimization techniques of grid connected photovoltaic system - Mamadou Traore; Alphousseyni Ndiaye; Senghane Mbodji (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
This paper presents the meta-heuristic and conventional optimizations techniques for the grid connected photovoltaic solar system. The perturb and observe (P&O) and particle swarm optimization (PSO) algorithms are proposed to track the maximum power point (MPP) of the photovoltaic solar system (PVSS). The regularization of the current supplied into the grid is ensured by the proportional integral (PI) corrector whose parameters are generated by the genetic algorithm (GA). The results of these two MPPT methods are compared and showed that the PSO is more efficient than the P&O. The use of GA algorithm to determine PI parameters allowed to obtain 0.89% of total distortion harmonic (THD).